Power-Generating Valleys on Territories Contaminated by radionuclides, Actinoids and Heavy Metals - G. A. Sharavarov; Z. P. Miniouk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Transformation of territories contaminated by radionuclides, actinoids, heavy metals and other harmful substances into power-generating valleys for production of pure bio-energy carriers is considered in the paper. The transformation process consists of three stages. The paper shows that the transformation of Belarussian territories contaminated as a result of Chernobyl accident into power-generating valleys will make it possible not only to provide our country with pure bio-energy carriers but also to make them import goods.